The Influence of Leadership and Spirit At Work Toward Commitment and Performance of The Employees at Hospital Level 4 01.07.04 Pekanbaru - Komarrudin, Moehammad Prijatna (International Journal of Economic, Business & Applications, 2017)
This study aims to find out how: 1) Leadership has positive impact and significant on employee commitment, 2) Spirit at work has positive impact and significant on employee commitment, 3) Employee commitment has positive impact on employee performance. This study used population of 82 employees at the Hospital Level IV 1.07.04 Pekanbaru with hypothesis census method was tested using analysis tools Partial Least Square. The results showed: 1) Leadership has positive impact and significant on the commitment, 2) Spirit at work has positive impact and significant on the commitment, 3) Commitment has positive impact and significant on employee performance at Hospital Level IV 01.07.04 Pekanbaru.